A Hybrid Electromagnetic–Triboelectric Energy Harvester Using a Dual Halbach Magnet Array Powered by Human‐Body‐Induced Motion. Issue 2 (21st December 2017) - Salauddin, Md; Cho, Hyunok; Park, Jae Yeong
Abstract: A highly miniaturized hybridization of electromagnetic–triboelectric energy harvesters with different mechanisms in one harvester is proposed using a Halbach magnet array from human‐body‐induced motion, and it is theoretically and experimentally validated. In particular, the proposed dual Halbach array allows the concentrated magnetic flux lines to interact with the same coil in a manner that produces maximum flux linkage. To obtain much higher power generation at low‐amplitude and low‐frequency vibrations, the proposed harvester is comprised of a Halbach magnet array, sandpaper‐based microstructure polydimethylsiloxane (PDMS), a triboelectric, and magnetic springs. A prototype of the hybrid energy harvester is fabricated and tested, both using a vibration exciter test, and by manual handshaking. Under vibration exciter test, the fabricated hybrid harvester prototype delivers a high output current and power of 4.5 mA and 12.51 mW, respectively, corresponding to a volume power density of 411 W m −3 under a loading resistance of 617 Ω at 6.5 Hz resonant frequency and 0.5 g acceleration. The hybrid prototype is also capable of delivering output current and power of 3.55 mA and 7.35 mW, respectively, if driven by handshaking vibration. The fabricated hybridized harvester exhibits much higher power density than similar recently reported works. Abstract : A human‐motion‐driven hybrid electromagnetic triboelectric energy harvester is designed, fabricated, and tested for scavenging significant power from handshaking vibration. The proposed harvester is comprised of a Halbach magnet array, sandpaper‐based microstructure PDMS, a triboelectric, and magnetic springs.